(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
30 years old, unmarried girl with above knee amputation of right lower limbs since 1998 as radical treatment for Osteosarcoma of upper tibia with no systemic or local recurrence after oncological treatment until now.